Analysis of Parameter Changes in Controlling the Quarter-car Active Suspension with PID Controller - Aprildy Randy Andrew Ferdinandus; Nindy Gaby Sepang (Jurnal Teknik Elektro dan Komputer, 2021)
Suspension is the part that connects the road surface and the car body, the car suspension is controlled by a control system to minimize car body vibrations caused by the road surface. In the operation of the car, there will be parameter changes that occur, among others, due to changes in the load of the car and tire pressure on the car and of course it affects the plant. The car suspension is controlled using the PID Controller simulated in the Simulink Matlab program and the parameters of the suspension are changed. With the change in suspension parameters, the results of control by the PID Controller can still control the suspension but there are differences in overshoot and settling time at the output